Review of bioequivalence studies of cholecalciferol drugs - Alexander L. Khokhlov; Dmitry P. Romodanovsky (Belgorod National Research University, 2020)
Introduction: The general requirements for assessing bioequivalence of endogenous drugs are described in the relevant guidelines, but they do not provide a complete picture of how to adequately develop a design of such a study. The aim of this article is to offer recommendations on the development of a design for bioequivalence studies of endogenous drugs, using cholecalciferol as an example. Materials and methods: A systematic review of our database on the results of bioequivalence studies of generic drugs revealed one study of cholecalciferol drugs, which was performed using a simple cross-over design. The study involved 24 healthy adult subjects. The data of 24 volunteers were retrospectively analyzed to identify endogenous cholecalciferol concentrations and intraindividual variability (CVintra) for Cmax and AUC0-t. As part of a retrospective analysis, we also assessed gender differences of pharmacokinetics. Results and discussion: Assessment of the bioequivalence of cholecalciferol drugs was complicated by the presence of endogenous concentrations of cholecalciferol for the tested drug - 1.27 (±0.55) ng/ml and for the reference drug - 0.98 (±0.55) ng/ml. The results of the analysis of the intraindividual variability of Cmax and AUC0-72 of the tested and reference drugs showed the following CVintra values - 22.80% and 21.58%, respectively. A comparative analysis of pharmacokinetic parameters did not reveal statistically significant gender differences. The article presents approaches to the planning of future bioequivalence studies of cholecalciferol drugs. Conclusion: Cholecalciferol is not a highly variable drug; however, it relates to drugs - analogues of endogenous compounds, which requires determining the endogenous concentrations.